Effect of induced hypoglycemia on inflammation and oxidative stress in type 2 diabetes and control subjects - Kahal, Hassan; Halama, Anna; Aburima, Ahmed; Bhagwat, Aditya M.; Butler, Alexandra E.; Graumann, Johannes; Suhre, Karsten; Sathyapalan, Thozhukat; Atkin, Stephen L. (Scientific reports, 2020)
Intensive diabetes control has been associated with increased mortality in type 2 diabetes (T2DM); this has been suggested to be due to increased hypoglycemia. We measured hypoglycemia-induced changes in endothelial parameters, oxidative stress markers and inflammation at baseline and after a 24-hour period in type 2 diabetic (T2DM) subjects versus age-matched controls. Case-control study: 10 T2DM and 8 control subjects. Blood glucose was reduced from 5 (90 mg/dl) to hypoglycemic levels of 2.8 mmol/L (50 mg/dl) for 1 hour by incremental hyperinsulinemic clamps using baseline and 24 hour samples. Measures of endothelial parameters, oxidative stress and inflammation at baseline and at 24-hours post hypoglycemia were performed: proteomic (Somalogic) analysis for inflammatory markers complemented by C-reactive protein (hsCRP) measurement, and proteomic markers and urinary isoprostanes for oxidative measures, together with endothelial function. Between baseline and 24 -hours after hypoglycemia, 15 of 140 inflammatory proteins differed in T2DM whilst only 1 of 140 differed in controls; all returned to baseline at 24-hours. However, elevated hsCRP levels were seen at 24-hours in T2DM (2.4 mg/L (1.2–5.4) vs. 3.9 mg/L (1.8–6.1), Baseline vs 24-hours, P < 0.05). In patients with T2DM, between baseline and 24-hour after hypoglycemia, only one of 15 oxidative stress proteins differed and this was not seen in controls. An increase (P = 0.016) from baseline (73.4 ng/mL) to 24 hours after hypoglycemia (91.7 ng/mL) was seen for urinary isoprostanes. Hypoglycemia resulted in inflammatory and oxidative stress markers being elevated in T2DM subjects but not controls 24-hours after the event.